The impact of long-term exposure to NO2, O3, and their oxidative potential on adolescents’ mental health, and the protective role of school-based greenness - Jiajia Dang; Yaqi Wang; Ning Ma; Shan Cai; Jianhui Guo; Yunfei Liu; Haoyu Zhou; Xinyao Lian; Di Shi; Ziyue Chen; Yihang Zhang; Jiaxin Li; et al. (Environment International)
Recent increases in nitrogen dioxide (NO2) and ozone (O3), two highly reactive and oxidative pollutants, have raised concerns about their potential impact on adolescent mental health. This study leveraged data from the Chinese National Survey on Students’ Constitution and Health (CNSSCH) in 2019, a nationally representative cross-sectional survey of Chinese adolescents. A total of 149,697 adolescents aged 10–18 years were included in this study. NO2 and O3 were sourced from the ChinaHighAirPollutants dataset, and the combined oxidative potential (OX) was subsequently calculated using the concentrations of NO2 and O3. The study quantitively examined the association of NO2, O3, and OX with adolescent mental health using the Dual Factor Model of Mental Health (DFM), which was derived from a questionnaire. According to the DFM, mental health status was divided into four groups: complete mental health, vulnerable, symptomatic but content, and troubled. Greenness around schools, measured by the Normalized Difference Vegetation Index (NDVI), was examined for its potential effect modification on the association between NO2, O3, OX, and mental health. Each IQR (Interquartile Range) increase in OX was related to adverse mental health outcomes, with ORs of 1.17 (95 % CI: 1.06, 1.29) for being vulnerable, 1.20 (95 % CI: 1.12, 1.28) for being more symptomatic but content, and 1.15 (95 % CI: 1.07, 1.23) for being troubled. Similar findings emerged in relation to O3 exposure. A positive association was observed between NO2 exposure and being vulnerable (OR = 1.07; 95 % CI: 1.01, 1.16). Additionally, the impact of exposure to NO2, O3, and OX on mental health outcomes was significantly stronger in the low-level NDVI group compared to the high-level NDVI group (P for interaction < 0.05). The joint effects analysis revealed that adolescents exposed to high levels of air pollutants and low NDVI had the highest odds of adverse mental health outcomes. These results highlight the complex relationship between NO2, O3, OX, and mental health, with particular emphasis on the underexplored role of OX. Notably, the findings suggest that reducing pollution and increasing greenery could offer significant benefits for improving adolescent mental health.